2015
DOI: 10.1051/0004-6361/201525799
|View full text |Cite
|
Sign up to set email alerts
|

Collisional quenching of highly rotationally excited HF

Abstract: Context. Collisional excitation rate coefficients play an important role in the dynamics of energy transfer in the interstellar medium. In particular, accurate rotational excitation rates are needed to interpret microwave and infrared observations of the interstellar gas for nonlocal thermodynamic equilibrium line formation. Aims. Theoretical cross sections and rate coefficients for collisional deexcitation of rotationally excited HF in the vibrational ground state are reported. Methods. The quantum-mechanical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
3
14
3
Order By: Relevance
“…However, a subsequent reconsideration by Shepler et al (2007) of the interaction potential employed suggested that the results of Balakrishnan, Yan, & Dalgarno (2002) are erroneous 1 . This is confirmed by a very recent paper by Yang et al (2013), which finds results for H 0 -CO collisions very similar to those of Green & Thaddeus (1976).…”
Section: Collision Rate Coefficientssupporting
confidence: 83%
“…However, a subsequent reconsideration by Shepler et al (2007) of the interaction potential employed suggested that the results of Balakrishnan, Yan, & Dalgarno (2002) are erroneous 1 . This is confirmed by a very recent paper by Yang et al (2013), which finds results for H 0 -CO collisions very similar to those of Green & Thaddeus (1976).…”
Section: Collision Rate Coefficientssupporting
confidence: 83%
“…It is explained that as the rotational quantum number increases, the energy gap between adjacent levels becomes larger and the energy transfer thus is inefficient. These quasi-resonant features of state-to-state ro-vibrational relaxation were also found in other rare gas-hydrogen fluoride (Rg-HF) [35] and H 2 -HF energy transfer systems [36].…”
Section: B Ro-vibrational Relaxationsupporting
confidence: 56%
“…We consider three collision partners for the RADEX models, namely atomic H, H 2 , and electrons. We use the new rate coefficients for the HF-H system by Desrousseaux & Lique (2018) which are provided between 10 and 500 K. Yang et al (2015) published rate coefficients for p-H 2 with HF for temperatures up to 3000 K. The previous coefficients for the HF-H 2 system provided by Guillon & Stoecklin (2012) are consistent with the more recent Yang et al (2015) results, and hence we use the coefficients of Guillon & Stoecklin (2012). Based on quantum mechanical calculations of collisional cross sections for the e-HF system by Thummel et al (1992) for T > 500 K, van der Tak et al (2012) estimated the excitation rate by electrons for HF ∆J = 1 at T < 500 K.…”
Section: Column Densitymentioning
confidence: 99%